Democratizing messaging? The role of ICTs in agriculture extension - Khan, Rashid Parvez (International Food Policy Research Institute, 2023)
Information and communications technology (ICT) in low- and middle-income countries has changed significantly over the past seven decades, starting with radio and newspapers and transforming almost daily with the rise of smartphones and mobile Internet. While ICT is an integral part of agricultural extension, little is known about how extension has been influenced by these changes in ICT. A systematic review of 133 papers focused on countries in South Asia, Southeast Asia, and sub-Saharan Africa found that changes in ICT have enabled a shift from linear dis semination and “one-way communication” to co-innovation and farmer-to-farmer learning, with the potential for increased democratization of agricultural extension. This note summarizes these findings.